Vertebrate consumption and dispersal of the Nothofagaceae associated ascomycete Cyttaria. (28th February 2019) - Elliott, Todd F.; Elliott, Kelsey
Abstract: Fungi are an important food source for a diversity of vertebrates and invertebrates around the world and in turn, these animals play a key part in the dispersal of many fungi. These associations have been most thoroughly studied between mammals and truffles. In this natural history note, we provide the first report of mycophagy by the Australian King‐Parrot ( Alisterus scapularis ) and the first documentation of wildlife consumption of the genus Cyttaria in Australia. We also review the literature regarding use of this southern hemisphere endemic genus Cyttaria for food by vertebrates and how these associations may impact its dispersal.